Oily Fish and Omega-3s Across the Life Stages: A Focus on Intakes and Future Directions - Derbyshire, Emma (Frontiers in Nutrition, 2019)
Background: There is a tendency to report oily fish intakes for adults collectively. This means that certain population groups tend to be overlooked. The purpose of the present article is to derive and evaluate oily fish and omega-3 intakes across the lifespan. Methods: A secondary analysis of the UK National Diet and Nutrition Survey (years 2008-2016) was undertaken. Data from n=2,949 participants ≥4 years was analysed. Alongside this, data was extracted from surveys published within the last 5-years reporting omega-3 intakes. Results: Overall, only a quarter (25.2%) of the UK population are oily fish consumers. Amongst those eating oily fish only 7.3% of children, 12.8% of teenagers and 15.6% of young adults (20-29 years) met oily fish recommendations. Mean intakes of oily fish ranged between 3.4 and 19.1g/day. Females aged 30-39 years and 60-69 years had significantly lower daily oily fish intakes than males (P=0.05 and P=0.049) although their intakes were higher than men in their fifties (P=0.048). Between 2008 and 2016 oily fish intakes have remained relatively stable although a significant decline was seen amongst those aged 50-59 years (P=0.048). Survey data (n=10 publications) showed that EPA and DHA intakes were consistently lower than guidelines, with children, teenagers, females and pregnant women having some of the largest dietary gaps. Conclusions: Younger generations, women of childbearing age and pregnant mothers appear to be at particular risk of oily fish and omega-3 shortfalls. Declining EPA and DHA profiles of farmed fish and plant-based food movements are only likely to exacerbate already inadequate intakes. Urgent public health campaigns are needed to improve UK intakes, which should include a combined approach of dietary and supplemental sources.